Effects of Time and Growth Media on Short-Chain Fatty Acid Production by Bacteroides fragilis - Mayhew, James W. (1975)
Gas-liquid chromatography was used to monitor the evolution of short chain fatty acids by Bacteroides fragilis in five media. Acetic and succinic acids, the prominent end products encountered, were readily detected within 24 h. Propionic, isobutyric, butyric, isovaleric, and lactic acids were usually recorded in more limited quantities. Maximum rates of bacterial multiplication, glucose catabolism, and end-product production coincided with the first 24 h in carbohydrate-supplemented media. Extended incubation (672 h) favored substantial succinate increases in three of five media. These observations suggest that incubation time and composition of the medium are important determinants in short chain fatty acid production by B. fragilis.